HUBUNGAN ANTARA SELF-ESTEEM DAN RESILIENSI PADA MAHASISWA PERANTAUAN DI UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA KAMPUS KOTA MADIUN - Mariska Aryono, Marcella; Tyas Leylasari, Herdina (Widya Warta, 2020)
This study aimed to determine the relationship between self-esteem and resilience among overseas students' at the Widya Mandala Catholic University Surabaya in Madiun Campus. This research used quantitative research with correlational methods. The samples of this study were 36 overseas students studying at the Widya Mandala Catholic University Surabaya in Madiun Campus. Data collection tools used in this study were Coopersmith Self-esteem Inventory and Connor-Davidson Resilience scale. Data analysis methods used were Product Moment correlation analysis and linear regression analysis. The data analysis results showed a close correlation between self-esteem and resilience among overseas students at the Widya Mandala Catholic University Surabaya in Madiun Campus. The relationship established was strong and positive in the same direction as indicated by a correlation coefficient of .674 at the significance level of .01 and R2 = .454 (F = 28.258; p = .000). It showed that there was a significant relationship between self-esteem and resilience among overseas students